Applying a mathematical model to simulate the ground water reservoir in Al-Alam area /Northeast Tikrit city/Iraq - Yasir Ahmed khudhair; Sabbar Abdullah Salih; Ghazi Atiya Zarraq (Tikrit Journal of Pure Science, 2021)
In this study, the water table in reservoirs in the Al-Alam area was studied for the year 2019. The water table was taken for 104 wells that covered the study area, except for the region near the Hemrin anticline, because it was impossible to reach for safety reasons. It was found that the higher water table North Study area near the Hemrin anticline and the levels decreased towards Al-Shari playa. A simulation of the aquifer was made after the introduction of the water table, the hydraulic properties of the area, and the depth of the reservoir. Three hypotheses were made to simulate the aquifer within one year by placing several virtual wells with constant drainage and the number of fixed operating hours during the year. to know the amount of water that leads to the depletion of the aquifer and the safe drilling distance of the aquifer. For the aquifer not to reach the stage of over-pumping and depletion, as several hypothetical wells have been placed in a manner that approximates the reality of the study area, Through a questionnaire on the number of working wells and relied upon in the study area, they were from about (250-350) wells. (200 wells, 300 wells, 400 wells) with constant discharge and operating hours during the year. As the well was operated according to the policies set by the Ministry of Agriculture with a discharge of (7 liters/second) for a period of (8 hours/day) for a period of (22.5 days/month), which is equivalent to (270 days/year) that is, at the disposal of (54432 m3 / year) for each A presumed well, to know the impact of the reservoir, and It was found that drilling 200 wells with a distance of 1 km2 between one well and another is considered safe and that drilling 300 wells or 400 wells in the study area leads to the depletion of the aquifer.